URGENSI PEDAGOGIK MULTILITERASI DALAM MEMBANGUN GENERASI EMAS 2045 YANG BERKARAKTER: URGENSI PEDAGOGIK MULTILITERASI DALAM MEMBANGUN GENERASI EMAS 2045 YANG BERKARAKTER - Madyaning Ratri, Titis; Muhtar, Tatang; Tri Herlambang, Yusuf (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Advances in technology and information that are developing very complexly make multiliteracy skills an important skill for generations to have in the 21st century. Efforts that can be made to improve human resources can be made by building a quality education system through the application of multiliteracy pedagogy. Multiliteracy pedagogy is an approach that assists students in developing broad literacy skills not only reading and writing, but becoming a meaningful learning for students. The method used in this study uses the library research approach, which is a series of activities related to the method of collecting library data, reading, taking notes, and processing research materials. Character education is a planned effort with the aim of making students strong, noble, moral, tolerant and have a spirit of mutual cooperation. The results of this study are that with the application of multi-terasi pedagogics, the inheritance of Indonesian cultural values ​​can be inherited so that it is hoped that the 2045 golden generation of Indonesia can actively participate in the international world which has the Pancasila character as a national cultural feature.